Holger Uhlich, Karel (C.A.J.) Kreutz & Stefan Rätzel (2015) A contribution to the taxonomy and phytogeography of Orobanche alba Steph. ex Willd. (Orobanchaceae). Phytotaxa 222 (1): 1–16. - Uhlich, Holger; Kreutz, C.a.j.; Rätzel, Stefan (Phytotaxa, 2015)
The authors present new knowledge on the biology and distribution of the poorly known Orobanche alba f. cuprea (= O. cuprea) and suggest its reclassification as a subspecies. Furthermore, the authors present recent data on biology and distribution of Orobanche alba subsp. xanthostigma. Distribution maps are shown for both taxa. Thymbra capitata and Thymus integer are recorded as new hosts for O. alba subsp. cuprea and Clinopodium vulgare s. l. for O. alba subsp. xanthostigma. Further information on the taxonomic assessment of other infraspecific taxa of O. alba are given as follows: O. alba f. maxima (= O. alba subsp. major) is promoted to the rank of variety based on a discovered earlier valid name; O. alba subsp. alba var. bidentata is rejected as an autonomous taxon and incorporated in the variability of the species.